Tinjauan Aturan Usia Minimal Pernikahan di Indonesia: Review of Minimum Marriage Age Regulations in Indonesia - Ngismatul Choiriyah; Ariyadi Ariyadi (Anterior Jurnal, 2025)
The dynamics of minimum age for marriage regulations in Indonesia have undergone significant changes following the enactment of Law Number 16 of 2019, which amended Law Number 1 of 1974. This amendment aims to reduce the number of early marriages and align with the protection of children's rights. This article aims to review the effectiveness of the minimum age regulation of 19 for men and women and to analyze its legal and sociological implications. This research uses a normative-juridical method with a statute approach. The results of the review indicate that, despite tightened regulations, a significant challenge persists due to the high number of marriage dispensation applications in Religious Courts. Cultural, economic, and religious factors hinder the law's optimal implementation. Therefore, synchronization between legal policy and widespread public education is needed to ensure that the primary goal of raising the minimum age for marriage can be substantively achieved.